2023
DOI: 10.31234/osf.io/c9jq6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scarcity Captures Attention and Induces Neglect: Eyetracking and Behavoral Evidence

Abstract: Scarcity poses challenging demands on the mind that can make escaping scarcity difficult. Using eyetracking and behavioral evidence, we find that scarcity induces an attentional focus, enhancing processing of scarcity-relevant information, while at the same time causing a failure to notice peripheral material, including information that may have proven beneficial in alleviating the scarcity condition. Participants were randomly assigned to a scarcity condition (with a small budget) or a control condition (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
4
2
0
Order By: Relevance
“…Instead, it appears that participants experiencing scarcity generally failed to notice bene cial information that could reveal the correct answer to the task and potentially alleviate their nancial burden. This aligns with prior work showing that scarcity can tunnel attention towards immediate and sure resource gains (Mullainathan & Sha r, 2014); constricting attention from more bene cial decision-making strategies that might better alleviate the experienced scarcity (Tomm & Zhao, 2016;.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Instead, it appears that participants experiencing scarcity generally failed to notice bene cial information that could reveal the correct answer to the task and potentially alleviate their nancial burden. This aligns with prior work showing that scarcity can tunnel attention towards immediate and sure resource gains (Mullainathan & Sha r, 2014); constricting attention from more bene cial decision-making strategies that might better alleviate the experienced scarcity (Tomm & Zhao, 2016;.…”
Section: Discussionsupporting
confidence: 87%
“…Albeit participants who experienced acute nancial scarcity behaved less unethically, they still displayed strong attentional bias towards the high-paying choice, while participants in a uence distributed attention more evenly on the screen (H2). This relationship aligns with prior evidence suggesting that experiences of scarcity can capture attention and direct focus towards choices that might aid in alleviating the experience of scarcity in the short term (Mani et al, 2013, Tomm & Zhao, 2016, although participants in this study ultimately do not act on this information. These results could suggest two things.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Although participants who experienced acute financial scarcity behaved less unethically, they still displayed strong attentional bias towards the high-paying choice, while participants in affluence distributed attention more evenly on the screen (H2). This relationship aligns with prior evidence suggesting that experiences of scarcity can capture attention and direct focus towards choices that might aid in alleviating the experience of scarcity in the short term (Mani et al, 2013;Tomm & Zhao, 2016), although participants in this study ultimately do not act on this information. These results could suggest two things.…”
Section: Discussionsupporting
confidence: 86%
“…Only one prior study has investigated how scarcity-induced focus regulation is manifested in gaze behavior (Tomm & Zhao, 2016). This study found that experiences of scarcity increased people's attention towards price-relevant information, which led to less attention towards beneficial discount information that could potentially alleviate scarcity.…”
Section: Resource Constraints Lead To Biased Attention But Decrease U...mentioning
confidence: 92%